2023
DOI: 10.1007/s11904-023-00661-1
|View full text |Cite
|
Sign up to set email alerts
|

Mpox and HIV: a Narrative Review

Abstract: Purpose of Review We reviewed the available literature on mpox in People with HIV (PWH). We highlight special considerations of mpox infection related to epidemiology, clinical presentation, diagnostic and treatment considerations, prevention, and public health messaging in PWH. Recent Findings During the 2022 mpox outbreak, PWH were disproportionally impacted worldwide. Recent reports suggest that the disease presentation, management, and prognosis of these patients, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…On the contrary, the evolution of Mpox in people living with HIV (PLWH) with a good viroimmunological status is more controversial. In fact, although previous data reported similar clinical outcomes in subjects with well-controlled HIV infections compared with subjects without HIV [ 27 , 28 , 29 ], a more protracted course of the disease [ 30 ] with a higher frequency of symptomatic diseases, particularly rash and anorectal symptoms/proctitis [ 31 , 32 ] and a greater utilization of healthcare resources and rates of hospitalizations [ 31 , 32 ] have been described in PLWH compared to their counterparts. Furthermore, an exuberant cutaneous presentation has been described in an acute HIV setting [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the evolution of Mpox in people living with HIV (PLWH) with a good viroimmunological status is more controversial. In fact, although previous data reported similar clinical outcomes in subjects with well-controlled HIV infections compared with subjects without HIV [ 27 , 28 , 29 ], a more protracted course of the disease [ 30 ] with a higher frequency of symptomatic diseases, particularly rash and anorectal symptoms/proctitis [ 31 , 32 ] and a greater utilization of healthcare resources and rates of hospitalizations [ 31 , 32 ] have been described in PLWH compared to their counterparts. Furthermore, an exuberant cutaneous presentation has been described in an acute HIV setting [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an exuberant cutaneous presentation has been described in an acute HIV setting [ 33 , 34 ]. These data suggest that an early start of Mpox antiviral treatments and pre-exposure prophylaxis in PLWH, regardless of immune status, might be important to prevent the progression to severe disease and complications [ 30 ]. Tecovirimat is an antiviral drug approved for smallpox treatment and currently authorized for Mpox [ 35 , 36 ] based on efficacy data in animal studies [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most cases in the current mpox outbreak are men who have sex with men (MSM), and the tightly connected sexual networks within this community might contribute to the rapid transmission of mpox 43 . Additionally, several reports from the US and Europe suggested that around 40% and up to 90% of mpox cases occurred in people with human immunodeficiency virus (HIV) 44 , resulting in more protracted and severe symptoms than those without HIV 45,46 . Therefore, there is an urgent need for the development of efficient therapeutics against MPXV, particularly for individuals who are living with HIV and exhibit poor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…44 Mpox patients with HIV infection are also more likely to develop severe Mpox cases. 45,46 Moreover, a study conducted in Chicago reported 70% of mpox patients were diagnosed with chlamydia and gonorrhea, and mpox patients with HIV infection had higher rates of chlamydia and gonorrhea than those without HIV infection. 47 Thus, people with HIV infection should be included in Mpox high-risk group.…”
Section: Possible Immunological Reasons For Mpox Breakthrough Infecti...mentioning
confidence: 99%
“…Results of a study which investigated the immunogenicity of Jynneos in HIV‐infected and uninfected people showed that the immune response levels and the growth rates of antibody titer in HIV‐infected people were both lower than those of HIV‐uninfected people 44 . Mpox patients with HIV infection are also more likely to develop severe Mpox cases 45,46 . Moreover, a study conducted in Chicago reported 70% of mpox patients were diagnosed with chlamydia and gonorrhea, and mpox patients with HIV infection had higher rates of chlamydia and gonorrhea than those without HIV infection 47 .…”
Section: Possible Immunological Reasons For Mpox Breakthrough Infecti...mentioning
confidence: 99%